Magadi tilapia ecological specialization: filling the early gap in the speciation continuum. Issue 7 (April 2016) - Pinho, Catarina; Faria, Rui
Abstract : Cichlid fish are well known for their high speciation rates, which are usually accompanied by spectacular and rapid diversification in eco‐morphological and secondary sexual traits. This is best illustrated by the famous repeated explosive radiations in the African Great Lakes Tanganyika, Malawi and Victoria, each lake harbouring several hundreds of mostly endemic species. Correspondingly, cichlids diversified very rapidly in many other lakes across their range. Although the larger radiations, unparalleled in vertebrates, are certainly the most intriguing, they are also the most intricate and difficult to address because of their complex nature. This is where smaller, simpler systems may prove to be the most useful. In this issue of Molecular Ecology, Kavembe et al . (2016 ) report very recent genetic diversification accompanied by ecological specialization in cichlids of the small and ecologically extreme Lake Magadi, in Kenya. Combining geometric morphometrics, stable isotope analysis, population genomics using RADSeq data and coalescent‐based modelling techniques, the authors characterize the eco‐morphological differences between genetically distinct populations of Magadi tilapia ( Alcolapia grahami ), which are consistent with the different environmental conditions they experience, and infer their history of divergence. The simplicity of the focal system and the use of a multidisciplinary approach make this work particularly important for our understanding of the early stages of speciation, in both cichlids and other organisms.